The educational consequences of migration for women and men: Migrant and Europe-born Turkish origin people compared to non-migrants in Turkey - Sait Bayrakdar; Ayse Guveli (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Research commonly compares the educational outcomes of migrants and the second generation to their native peers in destination countries, often finding the former groups lagging behind in education. Their outcomes are rarely compared to their non-migrant peers in the origin countries. Using the dissimilation from origins perspective, we ask whether Turkish-origin men and women in Europe benefit from migration by comparing their educational outcomes to non-migrants in Turkey. At the same time, we comparatively examine the intergenerational transmission of education to determine whether individuals are better off than their parents and grandparents. Analysing the novel 2000 Families data, we show that migrants and their descendants in Europe obtain higher education than their non-migrant peers in Turkey. While both men and women experience educational benefits from migration, women's gains are higher. Another salient finding is that Turkish-origin parents in Europe are less able to pass on their socioeconomic resources to their children than their counterparts in Turkey. Overall, the findings corroborate the theory of the dissimilation of Turkish-origin Europeans from their Turkish peers in educational attainment.
Keywords: 330; educational outcomes; international migration; gender; intergenerational transmissions; dissimilation